Occurrence of Infectious hematopoietic necrosis, Koi herpesvirus disease, and Viral hemorrhagic septicemia in North Macedonia between 2015-2023 - Trajchovski, Aleksandar; Dјadјovski, Igor; Krstevski, Kiril; Zagorka Popova Hristovska; Nikolovski, Martin; Angela Grujovska; Cvetkovikj, Aleksandar (Macedonian Veterinary Review, 2025)
Viral hemorrhagic septicemia (VHS), Infectious hematopoietic necrosis (IHN), and Koi herpesvirus disease (KHVD) are listed diseases by the European Commission that pose significant threats to the global aquaculture industry, resulting in substantial economic losses and impacting fish health and welfare. Due to their rapid spread potential, it is crucial for member states to implement measures preventing their transmission to disease-free areas. In this study, we aimed to assess the presence or absence of these viruses in fish aquaculture facilities in North Macedonia. During 9 years of surveillance from 2015 to 2023, 1,527 samples were tested for VHS and IHN, and 2,760 samples were tested for KHVD from aquaculture sites across North Macedonia using molecular diagnostic techniques. Our results indicated the absence of VHS and KHVD in all tested samples. However, the number of IHN-affected farms increased from two in 2018 to 33 by 2023, persisting across multiple sites. Despite the absence of VHS and KHVD, the ongoing presence and increasing incidence of IHN highlight the need to assess the effectiveness of existing biosecurity measures and disease management practices in the region. Ongoing surveillance and stringent biosecurity measures are essential for controlling IHN and preventing the introduction of other viral pathogens. Strengthening these measures is vital to ensure the long-term sustainability of the aquaculture industry in North Macedonia.
Keywords: Infectious hematopoietic necrosis; Koi herpesvirus disease; Viral hemorrhagic septicemia; epidemiology; North Macedonia